Systematics of the woody bamboos (tribe Bambuseae) - Ní Chonghaile, Gráinne (Trinity College (Dublin, Ireland). Department of Botany, 2002)
In this thesis the monophyly of the tribe Bambuseae and the inter-relationships of its constituents were assessed using comparative morphological character analysis and sequence analysis of four non-coding DNA regions, three of plastid origin (trnL intron, trnL-trnF spacer and the rpl16 intron) and one of nuclear origin (internal transcribed spacer (ITS) of rDNA). In the morphological analysis, the temperate woody bamboos were resolved as a monophyletic group. However due to an overall lack of defining characters, internal resolution with support was lacking. The molecular study provided support for a monophyletic woody bamboo lineage and temperate clade. However, support for a monophyletic tropical lineage and, furthermore, Palaeotropical and Neotropical sub-clades was lacking. In all datasets analysed the internal branches of the tropical bamboo lineages were well supported while those of the temperate clade were weakly supported. It is hypothesised that this feature may be attributed to one or a combination of factors; overtaxonomy, rapid radiation, sequence rate heterogeneity and/or recent radiation of the temperate bamboo lineage. All datasets proved informative at resolving evolutionary relations at the intergeneric level in the tropical bamboos. However, only one molecular dataset, the ITS dataset, proved informative at resolving relationships at the intergeneric level in the temperate clade.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin